Transforming The Furniture Industry in The Digital Age - Rame Rame; Purwanto Purwanto; Sudarno Sudarno (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
The furniture industry is experiencing a significant transition driven by digital technologies. This article comprehensively reviews various technologies, techniques, and innovations that the furniture industry has adopted to enhance efficiency, sustainability, and competitiveness. The analysis draws on a systematic literature review of recent publications in ScienceDirect and Scopus databases. The study highlights the potential of automation, robots, augmented reality, and the Internet of Things to improve the furniture production process, reduce waste, and boost profitability. Additionally, the article examines technologies and approaches that can help the furniture industry become more sustainable and socially responsible, such as green supply chain management, life cycle assessment, and ergonomic treatments. The paper concludes by advocating for a comprehensive digital transformation strategy that includes embracing new technologies, developing innovative business models, and promoting sustainability and ethical standards.